Public Aid and Its Particular Role in The System of State Aid in Poland and European Union (Concept of The Research) - Magdalena KOGUT-JAWORSKA (Communications of International Proceedings, 2021)
Public  aid  is  a  particular  kind  of  support  provided  by  the  state  to  economic  operators.  This  aid  can  be  granted  to  finance,  among  others,  the  projects  co-financed  with  UE  funds, specialized  advisory and training services, tax subsidies. Public aid is provided first of all for the development of micro, small and  medium-sized  enterprises  (businesses). There still lacks an answer to fundamental questions concerning the actual role of public aid in supporting business development, the role of self-governmental institutions offering such support, and the assessment of the impact, and the assessment of the impact resulting from the aid on economic condition of the beneficiaries. This research is most probably one of the few analyses to give answer to these essential questions. The paper attempts to explore the new fields for research where strong theoretical, methodological and empirical tools are lacking. Such circumstances are of essential importance at establishing the main objectives and tasks for the research. The general substantive justification for doing the research results from the following assumptions: In the last years, there have been very few theoretical attempts referring to the evolution of public aid forms, particularly the aid from self-government territorial units. However, the actual level of interface by the self-government has been growing in the same time. It is stressed that there lack detailed theoretical and empiric analyses on possibilities of application of public aid instruments at the both, local aid instrument at the both, local and regional levels after Poland’s EU accession (referring to particular beneficiaries, including small and middle – size companies or referring to particular economic entities being influenced, e.g. existing business people or potential national and international investors There is a necessity to perform updated and detailed research which will enable to give answers to the questions which forms of public aid have the broadest scope of influence on companies, which results for the local economy are brought about by particular solutions and when public aid should be stopped 4. There is a necessity to work out model solutions in order to apply new procedures for particular instruments and to introduce methodology in order to create a complete system of influencing local businesses. The new solutions and procedures can be applied to enhance practical solutions for self-governments in the near and more distant future.
Keywords: Public Aid; Eu Financial Policy; Economic Development; Entrepreneurship